Comparison of Simple and Segmented Linear Regression Models on the Effect of Sea Depth toward the Sea Temperature - Nirwana, Muhammad Bayu; Wulandari, Dewi (Enthusiastic : International Journal of Applied Statistics and Data Science, 2021)
The linear regression model is employed when it is identified a linear relationship between the dependent and independent variables. In some cases, the relationship between the two variables does not generate a linear line, that is, there is a change point at a certain point. Therefore, themaximum likelihood estimator for the linear regression does not produce an accurate model. The objective of this study is to presents the performance of simple linear and segmented linear regression models in which there are breakpoints in the data. The modeling is performed onthe data of depth and sea temperature. The model results display that the segmented linear regression is better in modeling data which contain changing points than the classical one.Received September 1, 2021Revised November 2, 2021Accepted November 11, 2021